To What Extent Business Excellence Dimensions Affect the Resilience and Performance of Qatari Enterprise: A Conceptual Report - Ahmed Abdullah Ahmed; Anita Ismail (Lattice Science Publication (LSP), 2024)
Non-Indexed Publication